BENZOPHENONE GLUCOSIDE ISOLATED FROM THE ETHYL ACETATE EXTRACT OF THE BARK OF MAHKOTA DEWA [Phaleria macrocarpa (Scheff.) Boerl.] AND ITS INHIBITORY ACTIVITY ON LEUKEMIA L1210 CELL LINE - Hendig Winarno; Ermin Katrin W (Indonesian Journal of Chemistry, 2009)
Isolation and elucidation of benzophenone glucoside from ethyl acetate extract of Phaleria macrocarpa bark and its inhibitory activity test against leukemia L1210 cell line have been done. The Phaleria macrocarpa bark were macerated using n-hexane, ethyl acetate, and ethanol, respectively. The ethyl acetate extract was then chromatographed on silica gel column and gradiently eluted by n-hexane - ethyl acetate - ethanol with the composition from 20:1:0 until 0:0:1, gave eight fractions. Separation of fraction 6 using semipreparative HPLC on reverse phase column (Capcell Pak C-18 SG120, 15 mm I.D. x 250 mm) using methanol - water (40:60, 5 mL/min) gave a brown powder, with the melting point of 182.3 ºC. Spectroscopic analysis and comparison of its physico-chemical data, this compound was clarified as 2,4'-dihydroxy-4-methoxy-benzophenone-6-O-b-D-glucopyranoside (3). Inhibitory activity of its compound against leukemia L1210 cell line showed that this compound exhibited inhibitory activity with IC50 was 5.1mg/mL.